Analysis and Design of Employee Attendance Application System Using RFID E-KTP Technology with ICONIX Process Method - Farizd, Mohammad; Pradana, Brillyan Putra; Shahita, Dwi; Ana Wati, Seftin Fitri (Inform : Jurnal Ilmiah Bidang Teknologi Informasi dan Komunikasi, 2022)
Attendance is an essential reference for the quality of human resources, including those who will carry out an activity, such as employees and supervisors. In carrying out these attendance activities, some still use it manually, such as recording in a detailed book, and its storage is still classified as conventional. Therefore, an employee attendance system that can record and manage data easily can be done quickly, efficiently, and accurately. This paper aims to analyze and design an employee RFID attendance information system using the ICONIX Process method. This RFID system is made using an RFID E-KTP supported by a database, where the RFID E-KTP is very easy to use. The results of this study are the analysis and design of an information system for implementing an employee attendance system based on RFID technology. The scope of information includes records of arrival times and return times. The results of the analysis and research design can be implemented properly in accordance with the proposed business process and can be a recommendation for various business actors to record employee attendance activities using RFID on the E-KTP.